2006
DOI: 10.1063/1.2180748
|View full text |Cite
|
Sign up to set email alerts
|

Advances in measurement and modeling of the high-confinement-mode pedestal on the Alcator C-Mod tokamak

Abstract: Edge transport barrier (ETB) studies on the Alcator C-Mod tokamak [Phys. Plasmas 1, 1511, (1994] investigate pedestal scalings and radial transport of plasma and neutrals.Pedestal profiles show trends with plasma operational parameters such as total current I P .A ballooning-like I 2 P dependence is seen in the pressure gradient, despite calculated stability to ideal ballooning modes. A similar scaling is seen in the near scrape-off-layer for both low-confinement (L-mode) and H-mode discharges, possibly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
73
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(88 citation statements)
references
References 39 publications
15
73
0
Order By: Relevance
“…The growing difference in H-mode plasmas between the n B 5+ pedestal location for the LFS and HFS isn't just a simple shift, but rather the pedestal width on the LFS is also increasing with q 95 , similar to electron density pedestal behavior 26 . For all the different regimes, the HFS boron density pedestal remains relatively fixed in width and position, while the LFS boron density pedestal width increases and the pedestal position shifts slightly inward depending on plasma parameters, as shown for the H-mode cases in Figure 8.…”
Section: In-out Asymmetries In the Pedestal Regionmentioning
confidence: 66%
“…The growing difference in H-mode plasmas between the n B 5+ pedestal location for the LFS and HFS isn't just a simple shift, but rather the pedestal width on the LFS is also increasing with q 95 , similar to electron density pedestal behavior 26 . For all the different regimes, the HFS boron density pedestal remains relatively fixed in width and position, while the LFS boron density pedestal width increases and the pedestal position shifts slightly inward depending on plasma parameters, as shown for the H-mode cases in Figure 8.…”
Section: In-out Asymmetries In the Pedestal Regionmentioning
confidence: 66%
“…170 These matches required DIII-D to operate at its lowest feasible H-mode densities, in a regime known to show a dependence of the pedestal width on neutral penetration 171 that is not seen on C-Mod, suggesting that the neutral penetration range can have an effect on sufficiently transparent pedestals. 172 However, C-Mod has the highest neutral opacity of any operating tokamak and should be more prototypical of ITER/ Reactor conditions.…”
Section: Eda H-modementioning
confidence: 99%
“…Pedestal studies on the Alcator C-Mod tokamak 1 have shown a clear correlation of edge particle transport, and resulting density pedestal structure, with plasma current. 2 Plasma transport appears to clamp edge density gradients, yielding a density pedestal that is strongly resilient to changes in the edge neutral source. 3 Finding mechanisms for breaking the correlation of H-mode density with current, thus allowing improved density control, is a key goal of C-Mod pedestal research.…”
Section: Introductionmentioning
confidence: 99%